Rare case of active lupus nephritis with mixed connective tissue disease in pregnancy - N., Sunanda; Ranjitha Madamakki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
This was a case report of a 32 years old pregnant woman with 9+6 weeks of gestation presented with hyperemesis gravidarum who was diagnosed of lupus nephritis with mixed connective tissue disorder (MCTD) 7 months back. Renal biopsy-lupus nephritis class 4 with activity score of 9/24 and chronicity score of 0/12. She was advised contraception in view of active lupus nephritis with MCTD but she presented to us with 9+6 weeks gestation with conception being within 20 days of her last dose of cyclophosphamide. She was managed with oral immunosuppressants by constant supervision of obstetricians and nephrologist. The management of MCTD and lupus nephritis in pregnancy presents a diagnostic and therapeutic challenge for providers. Women with prior lupus nephritis and MCTD can have safe, successful pregnancies with excellent, immaculate, collaborative care between obstetricians, nephrologists, and multidisciplinary staff.